'The Life of a Sailor' ('A Vida do Marujo'): A Portuguese and Brazilian Shanty. Issue 4 (2nd October 2021) - Marques, J. J. Dias
Abstract: This article deals with a folk song known as 'The Life of a Sailor' existing in Portuguese and Brazilian oral tradition. In this song, a sailor complains about the trials of his life on board, mainly the fatiguing tasks he has to perform, for low pay. Although it has been collected in some inland areas, it seems this song was used mainly as a shanty. It was included also in a danced theatrical play about maritime subjects, performed by sailors or fishermen, which is now lost in Portugal but continues in Brazil. This article studies the relationships of this song with three other songs: 'The Life of a Nun', 'The Life of a Friar', and 'The Life of a Student'. It also shows the view of life at sea which 'The Life of a Sailor' conveys, far removed from the epic tone usually connected with navigation in the Portuguese imaginary.